Patient Perspectives on Intravenous Biologics for Rheumatologic Disease. Issue 9 (7th August 2019) - Grisanti, Lucas; Kwiatkowski, Alysia; Dyrda, Peter; Field, Ellen; Grisanti, Joseph; Hatem, James; Dehoratius, Raphael J.; Gaylis, Norman
Abstract : Objective: Two surveys were conducted with patients with rheumatologic diseases to evaluate perceptions of different routes of administration (intravenous [IV] or subcutaneous [SC]) for biologic therapy. Methods: In Survey I, patient preferences toward biologic treatment were evaluated at a rheumatology practice in Buffalo, New York. In Survey II, Canadian patients enrolled in the BioAdvance patient support program and scheduled to receive IV biologic therapy were asked about their opinions of IV treatment. Results: In Survey I, 243 rheumatology patients participated. Median patient age was 60 years, 76% were female, and 44% were naive to treatment with biologic agents. Among biologic‐naive patients, the majority (56%) were open to either SC or IV treatment; biologic‐naive women were more likely than men to express a preference for the route of administration. In Survey II, 1, 598 patients from the BioAdvance program (including 306 rheumatology patients) completed the full survey. Among the rheumatology patients, the median age was 49 years, 58% were female, and 61% had not previously taken biologics before enrolling in the BioAdvance program. The median rating of IV favorability (on a 10‐point scale, with higher numbers indicating increased favorability) recalled by rheumatology patients was 5 prior to their first program infusion, which increased to 9 after multiple treatment infusions. Conclusion: These survey results indicate that patients with rheumatoid arthritis are generally open to IV treatment and express high satisfaction with IV therapy. Additional patient and provider education may improve shared decision‐making regarding biologic therapy administration options.